(untitled) (Bangladesh Journal of Agricultural Research, 2018)
The field experiment with nine Amaranthus cruentus genotype was conducted, to estimate the magnitude of genetic variability, heritability and genetic advance for leaf yield and contributing traits of amaranth genotypes during 2013 and 2017 cropping seasons. Field experiment was carried out in a randomized complete block design with three replications between 2013 and 2014 cropping season in Jalingo Taraba state. Data were collected on branches/plant, leaves/plant, leaf length, lead width, leaf fresh weight, leaf dry weight, marketable foliage yield, non- marketable foliage yield and plant height. Analysis of variance revealed highly significant mean squares (P< 0.01) among the genotypes tested for all the traits investigated. Thus indicating presence of high variability for foliage yield and yield traits. The PCV value was greater than GCV for all traits; however, GCV values were near to PCV values for the traits like leaf width, plant height branches/plant indicating high contribution of genotypic effect for phenotypic expression of such characters. High heritability coupled with high genetic advance per percent of mean reflect the presence of additive gene action in the expression of these traits, and improving of these traits could be done through simple selection.For multiple traits, AM 45 outperformed other genotypes for leaves/plant, fresh weight of leaves, plant height, and branches/plant.While AM 42 performed best for foliage yield (t/ha) and branches/plant. Bangladesh J. Agril. Res. 43(3): 513-524, September 2018